2018
DOI: 10.1515/med-2018-0068
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vancomycin in patients with different renal function levels

Abstract: AbstractThere are many determinants of vancomycin clearance, but these have not been analyzed separately in populations with different levels of renal function, which could be why some important factors have been missed. The aim of our study was to compare the pharmacokinetic parameters and factors that may affect vancomycin pharmacokinetics in groups of patients with normal renal function and in those with chronic kidney failure. The study used a population pharmacokinetic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(33 reference statements)
0
11
0
Order By: Relevance
“…However, to the best of our knowledge, the PPK model of vancomycin for Chinese infants based on different levels of renal function has not been proposed before. Zaric et al established a PPK model of vancomycin for adult patients with different renal function levels in 2018 ( 19 ), but this method has not been investigated among Chinese infants yet. So this study was the first one to conduct such an attempt.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, the PPK model of vancomycin for Chinese infants based on different levels of renal function has not been proposed before. Zaric et al established a PPK model of vancomycin for adult patients with different renal function levels in 2018 ( 19 ), but this method has not been investigated among Chinese infants yet. So this study was the first one to conduct such an attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of drugs less dialysable in HD requires the administration of antidotes or other techniques of blood purification, such as hemodiafiltration, plasma exchange, or plasma absorption (13). VCM has a relatively high molecular weight of 1,450 g/mol, protein binding of approximately 10%-50%, low Vd of approximately 0.4-1.0 L/kg, and high water solubility, while CFPM has a relatively low molecular weight of 571.5 g/mol, protein binding of approximately 16%-19%, low Vd of approximately 0.2 L/kg, and high water solubility (5)(6)(7)14). VCM was estimated to have a lower removal efficiency in HD than CFPM, as its molecular weight was higher than that of CFPM, although both drugs have low protein binding, low Vd, and high water solubility.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic characteristics of VCM are an approximately 80-90% excretion via urine, with a volume of distribution (Vd) of approximately 0.4-1.0 L/kg. In contrast, approximately 80% of CFPM is excreted via the urine, with a Vd of approximately 0.2 L/kg ( 5 - 7 ). VCM and CFPM were presumed to have a high transferability to ascites, since the ascitic concentrations of these drugs were increased after intravenous administration in patients with peritoneal dialysis and abdominal surgery ( 8 - 10 ), and the intravenous administration of these drugs was effective against peritonitis in peritoneal dialysis patients and spontaneous bacterial peritonitis in liver cirrhosis patients ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Renal excretion was reported to be 89% in healthy volunteers by Golper et al 45 Vancomycin is reabsorbed from kidney tubules by megalin receptors. 54,55 Drug interaction studies in rat showed lack of interaction with probenecid (OAT1) and nonsignificant interactions with cimetidine (MATEs and OCT2) and quinidine (P-glycoprotein). 56 In rabbit kidney tubules, vancomycin is actively secreted.…”
Section: Discussionmentioning
confidence: 99%